2019
DOI: 10.1159/000504482
|View full text |Cite
|
Sign up to set email alerts
|

Brusatol Protects HepG2 Cells against Oxygen-Glucose Deprivation-Induced Injury via Inhibiting Mitochondrial Reactive Oxygen Species-Induced Oxidative Stress

Abstract: Background: It has been reported that brusatol (BRU) reduces cellular reactive oxygen species (ROS) level under hypoxia; here the protective effect of BRU against oxygen-glucose deprivation/reoxygenation (OGD-R)-induced injury in HepG2 cells and against anoxia/reoxygenation (A/R)-induced injury in rat liver mitochondria was investigated. Materials and Methods: OGD-R-induced HepG2 cell viability loss was detected by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide and trypan blue staining. Mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In this study, we found that after PQ treatment of HepG2 G12V cells, changes of mitochondrial membrane permeability (MMP) and ATP synthesis were detected. In other studies, such as treatment of HepG2 cells with Brusatol, an increase in intracellular ROS has been reported, causing mitochondrial dysfunction, a reduction in ATP synthesis, and release of pro-apoptotic molecules to cause apoptosis (31). This is consistent with our findings, but whether PQ can affect other functions of HepG2 G12V cells was unknown.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that after PQ treatment of HepG2 G12V cells, changes of mitochondrial membrane permeability (MMP) and ATP synthesis were detected. In other studies, such as treatment of HepG2 cells with Brusatol, an increase in intracellular ROS has been reported, causing mitochondrial dysfunction, a reduction in ATP synthesis, and release of pro-apoptotic molecules to cause apoptosis (31). This is consistent with our findings, but whether PQ can affect other functions of HepG2 G12V cells was unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Brusatol is the first inhibitor in NRF2 signaling pathway. Recently, some researcher found that both intracellular ROS level and mitochondrial ROS level could be reduced by the treatment with brusatol, and brusatol also improved mitochondrial function and suppressed the release of cytochrome c, ameliorating the mitochondrial respiratory dysfunction caused by the overload of ROS [ 45 , 46 ]. However, why the downregulation of NRF2 could result in the mitochondrial protective effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that ROS can play either an immunostimulatory or an immunoinhibitory effect in the TME based on the type of cells from which it is produced and their specific location within the TME [ 47 , 48 ]. While ROS can induce ICD, increase tumor antigenicity, and reprogram tumor-associated macrophages, it also represents a major immunosuppressive mechanism when released by MDSCs or T-regs [ 49 , 50 , 51 , 52 , 53 ]. However, WFA was found to inhibit MDSCs production of ROS in a 4T1 mouse model suggesting that WFA plays a dual role in ROS signaling based on the cellular context [ 36 ].…”
Section: Discussionmentioning
confidence: 99%